2023
DOI: 10.1002/adhm.202203027
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Electric Field‐Coupled PD@BP Biomimetic Periosteum Promotes Bone Regeneration through Sensory Nerve via Fanconi Anemia Signaling Pathway

Abstract: To treat bone defects, repairing the nerve-rich periosteum is critical for repairing the local electric field. In this study, an endogenous electric field is coupled with 2D black phosphorus electroactive periosteum to explore its role in promoting bone regeneration through nerves. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are used to characterize the electrically active biomimetic periosteum. Here, the in vitro effects exerted by the electrically active periosteum on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 63 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…The electroactive field stimulates SCs into a neuroprotective phenotype, induces neurotransmitter release, and promotes osteogenic transformation. 194 Other metal elements, such as copper (Cu), tantalum (Ta), and calcium (Ca), are also beneficial to neurovascularization and bone regeneration. Researchers found that GelMA containing Cu 2+ -modified germanium-phosphorus (GeP) nanosheets (GelMA/GeP@Cu) were able to enhance nerve differentiation, axon regeneration, angiogenesis, and eventually enhanced osteogenesis.…”
Section: Referencementioning
confidence: 99%
“…The electroactive field stimulates SCs into a neuroprotective phenotype, induces neurotransmitter release, and promotes osteogenic transformation. 194 Other metal elements, such as copper (Cu), tantalum (Ta), and calcium (Ca), are also beneficial to neurovascularization and bone regeneration. Researchers found that GelMA containing Cu 2+ -modified germanium-phosphorus (GeP) nanosheets (GelMA/GeP@Cu) were able to enhance nerve differentiation, axon regeneration, angiogenesis, and eventually enhanced osteogenesis.…”
Section: Referencementioning
confidence: 99%
“…The nano-sheets with electric conduction released by BPNSs@mg and bioactive ions synergistically promote the migration and secretion of Schwann cell, which contributes to neural axon growth, and provide a new idea for neurogenic bone regeneration. Su et al ( Su et al, 2023 ) prepared a biomimetic periosteum using ordered coaxial electrospinning, and constructed an electrically active biomimetic periosteum by loading BPNSs onto the biomimetic periosteum via electrostatic action ( Figure 10 ). In this study, BP with excellent electrical conductivity was the main trigger to stimulate the efflux of nerve vesicles, then the PD@BP biomimetic periosteum mainly induces neurogenesis and osteogenesis through the Fanconi anemia pathway, providing a new strategy for bone regeneration.…”
Section: Applications Of Bp Nanoparticles For Os Therapymentioning
confidence: 99%
“…(E) Detection of electrically active periosteal osteogenesis with micro-CT in vivo . (Copyright ( Su et al, 2023 )).…”
Section: Applications Of Bp Nanoparticles For Os Therapymentioning
confidence: 99%
“…Several neuropeptides, which are secreted by sensory nerves, facilitate bone reconstruction [ 125 ]. Therefore, Su et al [ 126 ] utilized coaxial electrospinning technology to fabricate (core)–polycaprolactone (PCL)/s(shell)–DNM biomimetic periosteum(PD). BPNS combined with PD through electrostatic interactions, constructing an electrically active biomimetic bone membrane (BPNS/PD).…”
Section: Bp-based Composite Biomaterials For Tissue Repairmentioning
confidence: 99%